iRAD interactive radiology review & assessment - Chew, Felix S.; Kline, Mitchell J.; Whitman, Gary J.; Lippincott Williams & Wilkins (Philadelphia : Lippincott Williams & Wilkins, 2001)
(Producer) Provides a sequential case-based format with interactive questions. For instructing the user in diagnostic reasoning using radiologic images for patient care
CD is available at Koleksi Media, Perpustakaan HUKM
Approved for up to 60 hr. of CME credit in category 1 toward the AMA Physicians's Recognition Award, through Dec. 31, 2003
System requirements: Pentium 133 MHz or higher; 32 MB of RAM, 10 MB of free hard disk space; Windows 95, 98, or NT; thousands of colors, resolution 800x600; Netscape Navigator 4.6 or higher/Internet Explorer 5.0 or higher; CD-ROM drive
System requirements: Macintosh, PowerPC 63 or higher; 32 MB of RAM, 10 MB of free hard disk space; System 7.6.1 or higher; thousands of colors, resolution 800x600; Netscape Navigators 4.6 or higher/Internet Explorer 5.0 or higher; CD-ROM drive
Keywords: Diagnostic imaging; Radiology -- Examination questions